Studi Pemanfaatan Huma Betang Tumbang Anoi sebagai Sumber Pembelajaran Sejarah Lokal di Kalimantan Tengah - Kristanto V Baddak; Yulia Yustha; Manya Manya (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
A qualitative study has been carried out to determine the role of Betang Tumbang Anoi as a source of local history learning in Central Kalimantan Province. The study was conducted in Palangka Raya City and Gunung Mas Regency with respondents coming from high school history teachers in both regions. The results show that local history material is very important and although it is not explicitly contained in the K 13 curriculum, it can be given. Local history material does not conflict with the K 13 curriculum and even becomes part of K curriculum 13. Local history is important to be taught so that the younger generation is more familiar with their identities and increases their sense of nationality through local characters who are more down to earth. Learning local history also brings positive changes in students by introducing local history, among others, the growth of nationalism and historical awareness. Betang Tumbang Anoi as a peaceful meeting place Tumbang Anoi can be used as a source of local history learning in Central Kalimantan Province, but its use directly faces obstacles in the form of remote geographical location, poor transportation infrastructure and expensive travel costs. The use of Betoi Tumbang Anoi as a source of local history learning uses tools in the form of pictures or photographs obtained through the internet which are proven to be able to increase students' level of understanding.